VIA (Visual Inspection with Acetic Acid Aplication) Preparation of Steps - OCVIYANTI, DWIANA (Indonesian Journal of Cancer, 2010)
https://www.scribd.com/doc/43601359/VIA-Visual-Inspection-with-Acetic-Acid-Aplication-Preparation-of-Steps